Prebiotic-driven Gut Microbiota Dynamics: Enhancing Canine Health via Pet Food Formulation - Kumar, Rishav; Sharma, Ankit (International Journal of Bio-resource and Stress Management, 2024)
Expanding our understanding of canine nutrition is paramount for ensuring the well-being of our beloved companions. In recent years, there has been a paradigm shift towards recognizing the intricate interplay between diet and health outcomes in dogs. This shift has led to a surge of interest in exploring novel dietary interventions, with a focus on ingredients that can positively modulate the gut microbiota and enhance immune function. Prebiotics, defined as non-digestible food ingredients that beneficially affect the host by selectively stimulating the growth and/or activity of one or a limited number of bacteria in the colon, have emerged as key players in this domain. These substances, often found in fiber-rich foods such as fruits, vegetables, and whole grains, serve as fuel for beneficial gut bacteria, promoting their proliferation and diversity. By fostering a healthy gut microbiota, prebiotics contribute to improved nutrient absorption, reduced inflammation, and enhanced immune response in dogs. To fully realize the potential of prebiotics and symbiotics in canine nutrition, collaboration between veterinarians, animal nutritionists, and researchers is essential. By pooling expertise from diverse fields, we can design robust studies to investigate the efficacy of these interventions across different dog breeds, ages, and health conditions. Additionally, ongoing monitoring and surveillance are necessary to ensure the safety and efficacy of prebiotic and symbiotic products in the market. Through interdisciplinary efforts, we can harness the transformative power of advanced nutrition to enhance the lives of dogs and strengthen the human-animal bond for generations to come.